Does the intervention approach matter for improving 24-hour physical behaviours among overweight and obese Brazilian office workers? - Luiz Augusto Brusaca; Nidhi Gupta; David M. Hallman; Andreas Holtermann; Dechristian França Barbieri; Ana Beatriz Oliveira (BMC Public Health)
Abstract Background Physical behaviours over a 24-hour period are important for health. However, we do not know if interventions using a “24-hour time-use approach” are more effective in improving 24-hour time-use behaviours than the traditional “reduce sitting at work approach”. Thus, the aim of our non-randomised controlled study was to investigate this in a high-risk group of overweight and obese Brazilian office workers. Methods Forty-five office workers were allocated to three non-randomised controlled groups; “Reduce sitting at work” (n = 15) receiving an intervention focused on reducing sitting time at work; the “24-hour” (n = 15) receiving an intervention aiming to reduce sitting at work as well as promoting behavioural changes around 24 hours (e.g., sedentary lifestyle, benefits of physical activity, and healthy sleep hygiene); or “control” (n = 15) without any intervention. Daily time spent in physical behaviours (sitting, standing, active, and in bed) was monitored for 7 days using a thigh-worn accelerometer at baseline, and at the 3- and 6-month follow-ups. Intervention effects were analysed using linear mixed models, adjusted for baseline values, age, and sex, with a compositional data analysis approach. Results At baseline, the demographic characteristics and 24-hour physical behaviours of the groups were similar. No significant intervention effect was observed between the intervention groups for the overall 24-hour composition, except for time-in-bed, which decreased for Reduce sitting at work compared to 24-hour group from baseline to the 6-month follow-up (p-value = 0.02). Compared to the control group, both intervention approaches resulted in less time spent sitting, more time standing, and less time-in-bed from baseline to the 3-month follow-up, but these effects were not sustained at the 6-month follow-up. Notably, domain-specific (i.e., work and leisure) analysis revealed that most changes in the overall 24-hour composition occurred due to changes in behaviours during working hours. Conclusions Among Brazilian overweight and obese office workers, the “24-hour time-use approach” may not lead to better improvements in overall 24-hour composition of physical behaviours compared to the traditional “reduce sitting at work approach”.